Intensification of crop-livestock farming systems through market-orientation in Ethiopia - Tegegne, Azage; Hoekstra, Dirk; Gebremedhin, Berhanu; Berhe, Kahsay (International Livestock Research Institute, 2011)
Increasing food production and sustainable management of the natural resource base are key global challenges facing our world today and will continue to be so in the future. This is primarily due to population growth, increased urbanisation and higher incomes. Ethiopia has a land area of about 1.2 million Km2 and human population of about 80 million. The highlands, where integrated crop-livestock production systems dominate with varying intensities, occupy 35 % of the land and house 88 % of the human population and 74 % of the livestock resources. In the past, government support to subsistent production system with focus on cereal crops targeting household food security led to erosion-induced land degradation and plunged millions into poverty trap and food aid. In recent years, the Government of Ethiopia has taken a policy decision to transform subsistence mode of production into more market-oriented systems, and as a result the Improving Productivity and Market Succes (IPMS) project has been testing diﬀerent options of knowledge management, capacity building and crop and livestock commodity development strategies in support of market-oriented agricultural development in 10 pilot districts in four Regional States. These districts are ecologically contrasting and represent production systems ranging from extensive pastoral to varying intensities of integrated crop-livestock systems. Systematic and step-wise approaches were employed to assess the production systems and implement various interventions in production technologies, input supply system, marketing and support services such as extension and credit. Technological interventions coupled with appropriate organisational and institutional arrangements are critical factors for successful and sustainable intensiﬁcation of production systems through eﬃcient use of resources (land, water, nutrient and labour). A shift in policy is required to ensure participatory decision making based on available resources, technological options and choices, functional input and output markets, eﬃcient and eﬀective service delivery and farmers capacity to respond to climatic and market changes and their capacity to produce, process and market products. This paper explains the IPMS approaches, methods and processes used for eﬀective system integration and intensiﬁcation. The lessons learned provide valuable information for scaling up to other areas with similar potential for market-oriented agricultural development.